Дослідження чорноліського селища Єристівка ІІ на Кременчуччині у 2008 р. - Супруненко, О.Б.; Шерстюк, В.В. (Археологічні дослідження в Україні, 2010)
In 2008, protective excavations were conducted near Yerystivka village of Kremenchuk Region in Poltava Oblast on the area of 130 m2 at Chornoliska culture settlement Yerystivka II. The remains of two dwellings and six husbandry buildings probably of the late development stage of the culture; a series of ceramic fragments, stoneware, and bone products were obtained.